Layanan Bimbingan Kelompok Menggunakan Pendekatan Cognitive Behavioral Therapy (CBT) untuk Mengurangi Kecemasan Komunikasi Siswa Kelas XI SMK Baitul Hamdi Tahun Ajaran 2025/2026 - Lia Rosliana; Muhamad Ikhsan; Fitri Arnita (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2026)
The main problem addressed in this study is the high level of communication anxiety experienced by Grade XI students, particularly when speaking in public or expressing opinions in class. This condition negatively affects students’ self-confidence, learning process, and social interactions. This study aims to determine the effectiveness of group counseling services with a Cognitive Behavioral Therapy (CBT) approach in reducing students’ communication anxiety. The type of research used is quantitative with a quasi-experimental approach, employing a one-group pretest-posttest design. The population of this study consisted of all Grade XI students, while the sample was determined through purposive sampling, namely students with a high level of communication anxiety. Data were collected through observation, interviews, and questionnaires, and analyzed using normality testing and the Wilcoxon test. The results showed a significant difference in communication anxiety scores between the pretest and posttest. The Wilcoxon test revealed a significance value of 0.007 (< 0.05), indicating that there was a meaningful reduction in communication anxiety after the treatment. Thus, the research hypothesis was accepted. In conclusion, group counseling services using the CBT approach are effective in reducing students’ communication anxiety. The implementation of this service contributes to increasing self-confidence, enhancing public speaking skills, and supporting students’ academic success.